Time‐Lapse Microscopy Approaches to Track Cell Cycle and Lineage Progression at the Single‐Cell Level. Issue 1 (1st April 2013) - Errington, Rachel J.; Chappell, Sally C.; Khan, Imtiaz A.; Marquez, Nuria; Wiltshire, Marie; Griesdoorn, Victoria D.; Smith, Paul J.
Abstract: Time‐lapse microscopy can be described as the repeated collection of an image (in n ‐dimensions; x, y, z, λ) or field of view from a microscope at discrete time intervals. The duration of the time interval defines the temporal resolution, which in turn characterizes the type of event detected. This unit describes the implementation of time‐lapse microscopy to link initial cell cycle position during acute exposures to anti‐cancer agents with anti‐proliferative consequences for individual cells. The approach incorporates fundamental concepts arising from the ability to capture simple video sequences of cells from which it is possible to extract kinetic descriptors that reflect the interplay of mitosis and cell death in the growth of an unsynchronized tumor population. Utilizing a multi‐well format enables the user to screen different drug derivatives, multiple dose ranges, or cell cultures with unique genetic backgrounds. The objective of this unit is to present the basic methodology for capturing time‐lapse sequences and touch upon subsequent mining of the data for deriving event curves and possible cell lineage maps. Curr. Protoc. Cytom . 64:12.4.1‐12.4.13. © 2013 by John Wiley & Sons, Inc.